Design of portable stroke monitoring care in old human - Noimanee S. (2014)
The use of stroke monitoring to detect patient or old people with the intent to prevent patients dead after heart operation falls. This paper presents portable patient monitoring system laboratory prototype, which provides patient electrocardiogram signals transferring via mobile extension technology with old version mobile phone in Thailand. At the human location, a wireless old version mobile phone C45-based monitor is used to acquire continuously the patient's ECG, including stroke signal, etc. The system has been evaluated by physician verification and laboratory test. Through the mobile extension services in Thailand, the patient's stroke signals can be transmitted in real-time to a central management unit, and authorized medical staffs or physician can access the ECG and stroke wave form, data and the case history of each patient by mobile personal digital assistant or PC trough Wi-Fi technology, either by the central management unit or the wireless devices. The results were that the prototype reduced the risk of heart attack by 15%. Most benefit was due to 30% drop in the risk of heart-related death. Their also show that the mobile PDA is superior to the currently used monitors both in mobility and in usability, therefore, better suited to patient transport. ©2008 IEEE.